Influence of Au on Ge Crystallization and Its Thermoelectric Properties in a Au-induced Ge Crystallization Technique - Selvaraj, Shanthi; Khan, Faizan; Nishino, Shunsuke; Muthusamy, Omprakash; Takeuchi, Tsunehiro; Shimura, Yosuke; Hayakawa, Yasuhiro; Chellamuthu, Muthamizhchelvan; Ikeda, Hiroya (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Poly-crystalline Ge (pc-Ge) thin films were prepared on a SiO2/Si substrate using Au-induced crystallization (GIC) of amorphous Ge (a-Ge) with an annealing temperature around the eutectic point of Au-Ge alloy system (361ÂºC) in order to shorten the annealing time. Bilayer thin films of Au (20 nm)/a-Ge (100 nm) were used as a precursor material and annealed at 300, 400, and 500 ÂºC for 60 min, which successfully leads to the formation of pc-Ge layers. Characterizing the prepared Ge layers, the crystallographic properties indicated that the metal catalyst Au plays a notable role of enhancing both the crystallization and the island formation of Ge layers. It was also shown that the pc-Ge hardly contains Au atoms. Therefore, the Seebeck coefficient was hardly influenced by Au atoms since they do not act as a carrier source. In addition, the thermal conductivity of the pc-Ge film prepared by the GIC method was higher than that formed without Au, which is not due to the Au catalyst itself but due to the crystallinity of Ge film enhanced by the Au atoms.